Changes of PGC-1α/TFAM signaling pathway and mitochondrial dysfunction of renal tubular epithelial cells during sepsis-associated acute kidney injury - Xiao Zhen-meng; Li Zhi-lian; Dong Wei; Zhang Meng-xi; Chen Yuan-han; Li Rui-zhao; Liang Xin-ling (Linchuang shenzangbing zazhi)
Objective To explore the changes of signaling pathways of peroxisome proliferator-activated receptor γ coactivator 1α and mitochondrial transcription factor A and mitochondrial damage in renal tubular epithelial cells during sepsis-associated acute kidney injury（AKI）.Methods A murine model of septic AKI model was established after 8-10-week-old male C57 BL/6 mice received an intraperitoneal injection of lipopolysaccharide（LPS;10 mg/kg）.Serum levels of urea nitrogen, creatinine and kidney injury molecule 1 were measured at 24 h post-injection.Renal pathological damage was observed after periodic acid-Schiff（PAS）stain.Electron microscope was employed for observing the changes of mitochondrial morphology and count in proximal renal tubular epithelial cells.Western blot and real-time fluorescent quantitative polymerase chain reaction（PCR）were employed for detecting the mRNA/protein expression levels of LC3 II,p62,PGC-1α,TFAM and the ratio of mitochondrial DNA to nuclear DNA.In LPS-induced endotoxemia AKI model of renal tubular epithelial cell, PGC-1α and TFAM were measured by Western blot, RT-qPCR and immunofluorescence.MTT was utilized for detecting cell viability; mitochondrial membrane potential observed by JC-1;mitochondrial morphological change detected by MitoTracker and mitochondrial superoxide content assessed by Mito-SOXTM.Results As compared with control group, blood urea nitrogen, serum creatinine and kidney injury molecule 1 spiked markedly in model group.And proximal renal tubular epithelial cells had mild vacuolar degeneration and a greater transcription of inflammation and oxidative stress factors such as IL-1β,IL-6 and HMGB1.Under electron microscope, mitochondria in proximal renal tubular epithelial cells in model group became obviously swollen and rounded with broken ridges and more autophagosomes and the expressions of autophagy marker proteins LC3 II and p62 were up-regulated in kidney tissue（P<0.05）and the mRNA/protein expressions of PGC-1α and TFAM declined markedly（P<0.05）.The ratio of mitochondrial DNA to nuclear DNA（mtDNA:nDNA）declined in renal cortex tissues of LPS-injected mice as compared with control mice（P<0.05）.In vitro LPS stimulation lowered HK-2 cell viability and boosted mitochondrial dysfunction.The protein expressions of PGC-1α and TFAM declined with the rising concentration of LPS in HK-2 cells（P<0.05）.Conclusion The signaling pathway of PGC-1α/TFAM may be a novel intervention target for septic AKI.